2004
DOI: 10.1177/095624780401600105
|View full text |Cite
|
Sign up to set email alerts
|

Community federations and city upgrading: the work of Pamoja Trust and Muungano in Kenya

Abstract: SUMMARY: This paper describes the work of the Kenyan NGO Pamoja Trust and the urban poor federation in Kenya (Muungano wa Wanvijiji)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…This is in line with other definitions of community byNutbeam (1998), andFettes (1999), found inAllman (2015). For additional information on their activities, see section 7 and Karanja (2010),Makau et al (2012), andWeru (2004). One feature they share is that they engage in several core activities of the Kenyan federation of the urban poor with the aim of finding more cost-effective and sustainable solutions to housing, infrastructure, services, and livelihoods in these settlements.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…This is in line with other definitions of community byNutbeam (1998), andFettes (1999), found inAllman (2015). For additional information on their activities, see section 7 and Karanja (2010),Makau et al (2012), andWeru (2004). One feature they share is that they engage in several core activities of the Kenyan federation of the urban poor with the aim of finding more cost-effective and sustainable solutions to housing, infrastructure, services, and livelihoods in these settlements.…”
supporting
confidence: 74%
“…Inspired by many other examples of PGIS and community mapping elsewhere (e.g., Corbett et al, 2006;Livengood & Kunte, 2012), the Kenyan Federation of the Urban Poor (Muungano wa Wanavijiji) has been using PGIS for profiling, enumeration, and mapping of urban informal settlements (for examples, see Karanja, 201;Makau et al, 2012;and Weru, 2004). They have had long-term support in community profiling from Shack/Slum Dwellers International (SDI), 3 which also supports similar federations in 33 countries and 488 cities across Africa, Latin America, and Asia.…”
Section: Participatory Gis and Community-led Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…Much research in the area of urban development studies has shown how state-driven regeneration programmes have resulted in displacement and gentrification (Bassett et al, 2003;Campbell, 1990). In contrast, other studies have shown how communities self-organize to demand public services, and have praised the collective action of disadvantaged urban communities in pursuit of their own development (Appadurai, 2001;D'Cruz et al, 2009;Mitlin, 2008;Weru, 2004). Despite their different approaches and conclusions, these two bodies of work share an exploration of the relationships between 'the state' (or other development agencies) and 'communities'.…”
Section: Introductionmentioning
confidence: 99%